Squarate-tethered enantiomeric Imido-Pd(II) cages for recognition and separation of chiral organic molecules - Jose, Cavya; Sarkar, Meghamala; Rajasekar, Prabhakaran; Tewari, Tanuja; Boomishankar, Ramamoorthy (Inorganic Chemistry, 2023)
Chiral coordination cages have emerged as an efficient platform for enantioselective processes via host-guest interactions. Here, we report an enantiomeric pair of tetrahedral cages of formula [(Pd-3[PO(N(*CH(CH3)Ph)(3)])(4)(C4O4)(6)] supported by chiral tris(imido)phosphate trianions and squarate (C4O4)(2-) linkers. These cages exhibit unusual coordination isomerism for Pd(II)-linker bonds compared with the other Pd(II) cages of this family. Further, they were employed for the recognition and separation of small chiral molecules containing various functionalities. High enantioselectivities of 67 and 41 were found in the case of R-4-hydroxydihydrofuran-2(3H)-one and S-epichlorohydrin, recognized by the R-isomer of the cage. Chiral separation studies showed remarkable enantiomeric excess values of 93 and 85% for S-epichlorohydrin and R-4-benzyl-2-oxazolidinone, respectively, from their racemic mixtures. These studies showcase the potential of coordination cages for enantioselective applications.